The beverage manager's guide to wines, beers, and spirits - Schmid, Albert W. A.; Laloganes, John Peter (Boston, Massachusetts : Pearson, 2013)
This book takes the reader on an intriguing journey that explores the essential aspects of wine, beer, and spirits while providing marvelous insights along the way.
1. The evolution of alcoholic beverages -- 2. Alcohol safety and professional beverage service -- 3. Viticulture: Outside in the vineyard -- 4. Enology: Inside the winery -- 5. Wine regulations and labeling methods -- 6. The wine styling approach -- 7. Other wines: Sparkling, fortified, and dessert wines -- 8. The brewery: Beer production and other fermented beverages -- 9. Ales and lagers of the world -- 10. The distillery: Spirits and liquers of the world -- 11. Mixology: The art and science of the cocktail -- 12 Constructing the beverage concept -- 13. Managing for profit -- Marketing the beverage establishment
Includes index.
Keywords: BARTENDING